Are there consistent abnormalities in event‐related EEG oscillations in patients with Alzheimer's disease compared to other diseases belonging to dementia?. (30th August 2021) - Güntekin, Bahar; Aktürk, Tuba; Arakaki, Xianghong; Bonanni, Laura; Del Percio, Claudio; Edelmayer, Rebecca; Farina, Francesca; Ferri, Raffaele; Hanoğlu, Lütfü; Kumar, Sanjeev; Lizio, Roberta; Lopez, Susanna; et al.
Abstract: Cerebrospinal and structural‐molecular neuroimaging in‐vivo biomarkers are recommended for diagnostic purposes in Alzheimer's disease (AD) and other dementias; however, they do not explain the effects of AD neuropathology on neurophysiological mechanisms underpinning cognitive processes. Here, an Expert Panel from the Electrophysiology Professional Interest Area of the Alzheimer's Association reviewed the field literature and reached consensus on the event‐related electroencephalographic oscillations (EROs) that show consistent abnormalities in patients with significant cognitive deficits due to Alzheimer's, Parkinson's (PD), Lewy body (LBD), and cerebrovascular diseases. Converging evidence from oddball paradigms showed that, as compared to cognitively unimpaired (CU) older adults, AD patients had lower amplitude in widespread delta (>4 Hz) and theta (4–7 Hz) phase‐locked EROs as a function of disease severity. Similar effects were also observed in PD, LBD, and/or cerebrovascular cognitive impairment patients. Non‐phase‐locked alpha (8–12 Hz) and beta (13–30 Hz) oscillations were abnormally reduced (event‐related desynchronization, ERD) in AD patients relative to CU. However, studies on patients with other dementias remain lacking. Delta and theta phase‐locked EROs during oddball tasks may be useful neurophysiological biomarkers of cognitive systems at work in heuristic and intervention clinical trials performed in AD patients, but more research is needed regarding their potential role for other dementias. Abstract : A multidisciplinary Expert Panel reviewed the literature and reached a consensus on the event‐related electroencephalographic oscillations (EROs) showing consistent abnormalities in patients with significant cognitive deficits due to Alzheimer's, Parkinson's (PD), Lewy body (LBD), and cerebrovascular diseases. Delta and theta phase‐locked EROs during oddball tasks may be useful as neurophysiological biomarkers of cognitive systems at work in AD patients, although those EEG measures were unspecific in relation to the other dementing disorders mentioned above.